Showing/Sharing: Analysing Visual Communication from a Praxeological Perspective - Schreiber, Maria (Media and Communication, 2017)
This contribution proposes a methodological framework for empirical research into visual practices on social media. The framework identifies practices, pictures and platforms as relevant dimensions of analysis. It is mainly developed within, and is compatible with qualitative, interpretive approaches which focus on visual communication as part of everyday personal communicative practices. Two screenshots from Instagram and Facebook are introduced as empirical examples to investigate collaborative practices of meaning-making relating to pictures on social media. While social media seems to augment reflexive, processual practices of negotiating identities, visual media, in particular, amps up aesthetic, ambivalent and embodied dimensions within these practices.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTc2NDUvbWFjLnY1aTQuMTA3NQ